Sobre os processos de tessitura dos currículos no ensino médio : as marcas das negociações, das experiências e dos hibridismos vividos nos cotidianos - Barcellos, Adriana Pionttkovsky (2016)
The text presents a research concerning the curriculum organization of a public state school of Espírito Santo, Brazil emphasizing marks of the experiences, the negotiations and the hybridizations that are established in the daily practices of High School. It seeks to follow a bit of the knowledge, doings, values and powers networks that are shared by the practitioner subjects that operate in these spaces and times as power to curriculum discussions. It states that the curriculum policies express the power of the complexity of these networks beyond of what is established in the documents and / or curriculum prescriptions, considering that everyday life is not limited nor let itself be captured by the logic of the official proposals. It invests in the relevance of the study presented as a clue to the understanding that the curricula practiced in school daily routines are constituted as anonymous creations produced in teachers, students and other practitioners‟ operations. It emphasizes, therefore, that the curricula are woven in these ordinary relations with exchange of demonstrations, negotiation and the various practices that involve power, creation of meanings and cultural joints. It takes as a methodological political theoretical perspective the research practices within daily life and, accordingly, uses observations, documents, conversations, records, narrativesimages as research procedures. It also defends that the curriculum organizations are given in the negotiations, experiences, and hybridizations that permanently are lived among the subjects in their curricular practices and theories, negotiating the difference by asserting their heterogeneity and performativity, by escaping from the prescriptions, by repeating established models, by creating rules, by teasing the systems of control, by establishing inventiveness, finally by living the complexity of this mixture of meanings, sounds, images, ways to "make with" inherent to school life.